2011
DOI: 10.1097/nnr.0b013e3182337d83
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Suicidal Ideation Among Taiwanese Adolescents

Abstract: : Suicidal ideation prevention programs should be targeted to female adolescents. School-based efforts that provide adolescents with self-esteem enhancement, emotional regulation skills training, positive peer norms for life, coping skills for managing stress and depression, and antibullying programs might help reduce the suicidal ideation of adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 30 publications
3
22
0
1
Order By: Relevance
“…According to Lazarus and Folkman's (1984) cognitive-transactional stress theory, appraisal and interpretation of the event is more important than the event itself. Several studies have found a direct relationship between stress and suicidal ideation among nurses (Aradilla-Herrero, Tomás-Sábado, & Gómez-Benito, 2014;Wang, Lai, Hsu, & Hsu, 2011); however, the relationship between stress and suicidal ideation among Malaysian nursing student has not been investigated.…”
mentioning
confidence: 99%
“…According to Lazarus and Folkman's (1984) cognitive-transactional stress theory, appraisal and interpretation of the event is more important than the event itself. Several studies have found a direct relationship between stress and suicidal ideation among nurses (Aradilla-Herrero, Tomás-Sábado, & Gómez-Benito, 2014;Wang, Lai, Hsu, & Hsu, 2011); however, the relationship between stress and suicidal ideation among Malaysian nursing student has not been investigated.…”
mentioning
confidence: 99%
“…However, the measure was adopted from the US youth risk behavior survey (YRBS) [34]. This single item has been widely used in American and European young students (European School Survey Project on alcohol and other drugs) [35], in the WHO international survey for school-aged children (Health behavior in school-aged children study, HBSC) [36], in the Korea youth (Korea Youth Risk Behavior Web-based Survey, KYRBWS) [37], in Mexico city [38], and in Chinese adolescents in Taiwan [39-41]. We believed this single item had its value even though it was not perfect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the evidence supporting the link between attitudes towards suicide and risk of suicide, consistent relationship has been found between measures of mental health status and suicidal ideation (Caldwell et al ; Hintikka et al ; Nurka & Amila ; Amanda et al ; Milner et al ; Sobowale et al ). Mental health problems, commonly consisting of neuroses and psychoses, constitute one of the risk factors for suicidal behaviour (Phillips et al ; Lei et al ; Wang et al ; You et al ). Nevertheless, most individuals who experience mental health problems never make a suicide attempt.…”
Section: Introductionmentioning
confidence: 99%